가정식, 급식, 외식 고나트륨 한식 대표 음식의 염도 분석 - 지앙린(Lin Jiang); 신다민(Damin Shin); 이연경(Yeon-Kyung Lee) (Korean journal of community nutrition, 2018)
Objectives: This study was conducted to analyze the salinity of representative Korean foods high in sodium to generate data for use as a fundamental resource for setting salinity standards in foods. Methods: A total of 480 foods from 16 representative Korean foods high in sodium were collected from 10 households, 10 industry foodservice establishments, and 10 Korean restaurants in four regions (Capital area, Chungcheong Province, Gyeongsang Province, and Jeolla Province) and analyzed for salinity. Results: Among the foods, stir-fried anchovies (4.07~4.45%) showed the highest salinity, followed by pickled onion (1.86~2.62%), cabbage kimchi (1.83~2.2%), braised burdock and lotus root (1.79~2.17%), and sliced radish kimchi (1.78~1.89%) (p<0.001). The salinity of kimchi from home meals (2.2%) was significantly higher than that of foodservice (1.83%) and restaurant (1.93%) kimchi (p<0.05). Salinity in each group of food was highest in kimchi (1.83~2.04%), followed by braised dishes (1.54~1.78%), steamed dishes (1.0~1.22%), stir-fried dishes (1.02~1.18%), and soup or stew (0.74~1.02%) (p<0.001). The salinity of soup and stew from restaurants (1.02%) was significantly higher than that of home meal (0.84%) and foodservice (0.74%) soup and stew. Conclusions: Determination of the salinity of representative Korean foods known to be high in sodium by eating place is expected to be useful to establishing guidelines for reduction of salinity.